Mastering Microsoft Visual Basic 2005 - Petroutsos, Evangelos; Microsoft Corporation (Indianapolis, IN : Wiley Pub., 2006)
"This book shows you how to use Visual Studio 2005 and Visual Basic 2005 to design rich Windows and Web applications."--p. [xxv].
Includes index.
" An earlier version of this book was published under the title 'Mastering Visual Basic .NET', 2002"--T.p. verso.
"SYBEX"--Cover.
Keywords: BASIC (Computer program language); Microsoft .NET Framework